2021
DOI: 10.1002/ptr.6979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of watercress extract supplementation on lipid profile and oxidative stress markers in overweight people with physical disability: A randomized, double‐blind, and placebo‐controlled trial

Abstract: Studies have demonstrated that diet rich in cruciferous vegetables of the Brassicaceae family can reduce the risk of cardiovascular diseases and oxidative stress levels. Nasturtium officinale (Brassicaceae), commonly known as watercress is a perennial dicotyledonous plant usually found close to water. Although previous investigations have demonstrated the beneficial effects of watercress on hypercholesterolemia in animal studies, until now no such studies have been conducted with humans, up to this time. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Many studies are in consistent to our results [41,53]. Previously published data show that NOE consumption significantly increases the activity of SOD enzyme [54]. is study also confirmed that NOE had an effect on the GPX and SOD activity in the group A + NOE compared to group A. ese findings increased the knowledge of the antioxidant effects of NOE, in which, the phenolic compounds stimulate GPX activity, thus reducing the free radical accumulation [55].…”
Section: Evidence-based Complementary and Alternative Medicinesupporting
confidence: 90%
See 1 more Smart Citation
“…Many studies are in consistent to our results [41,53]. Previously published data show that NOE consumption significantly increases the activity of SOD enzyme [54]. is study also confirmed that NOE had an effect on the GPX and SOD activity in the group A + NOE compared to group A. ese findings increased the knowledge of the antioxidant effects of NOE, in which, the phenolic compounds stimulate GPX activity, thus reducing the free radical accumulation [55].…”
Section: Evidence-based Complementary and Alternative Medicinesupporting
confidence: 90%
“…Many studies are in consistent to our results [ 41 , 53 ]. Previously published data show that NOE consumption significantly increases the activity of SOD enzyme [ 54 ]. This study also confirmed that NOE had an effect on the GPX and SOD activity in the group A + NOE compared to group A .…”
Section: Discussionmentioning
confidence: 99%